Six Decades of Indonesia-China Relations An Indonesian Perspective (Springer Singapore, 2018)
This book analyses the relations between Indonesia and China in the regional dynamics of Southeast Asia. The rising China has influenced global and regional constellations, and also has direct impacts for Indonesia. While this fact should be viewed as an opportunity that needs to be fully utilised for the benefit of national development of Indonesia, we should also prepare for the threats embedded in this development, especially from the service and labour sectors. As such, this book suggests that equal positions in relations between Indonesia and China are absolutely necessary, since both countries need each other in their efforts to maintain the continuity of their development. It also argues that to further strengthen its position in relation to China in the future, Indonesia's diplomacy requires an integrated grand design that supports the creation of economic and political power in the face of the emergence of China's economic and military power. .